2017
DOI: 10.1371/journal.pone.0188019
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between shift work and mental health among electronics workers in South Korea: A cross-sectional study

Abstract: ObjectiveTo determine the relationship between shift work and mental health, particularly insomnia, depression, and suicidal ideation, among electronics production workers.MethodsA survey was conducted with 14,226 workers from an electronics manufacturer in South Korea. After excluding 112 individuals with incomplete responses, 14,114 respondents were analyzed. As part of a larger project, we collected data on respondents’ general characteristics, work-related characteristics, and health status; however, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 28 publications
5
39
4
Order By: Relevance
“…Notably, our result indicated that one-third of our sample had suicidal ideation in the last two weeks, which was more than four times higher when compared with the rate of suicidal ideation in the general Vietnamese population (8.9%) [36]. This prevalence was significantly higher than that in other settings such as the United States (2.6%) [37] and Korea (2.8%) [38]. Prior literature revealed that industrial workers were particularly vulnerable populations to depression and other mental health disorders given their low education and income, highly repetitive work, and constrained social support [6,39].…”
Section: Discussioncontrasting
confidence: 48%
“…Notably, our result indicated that one-third of our sample had suicidal ideation in the last two weeks, which was more than four times higher when compared with the rate of suicidal ideation in the general Vietnamese population (8.9%) [36]. This prevalence was significantly higher than that in other settings such as the United States (2.6%) [37] and Korea (2.8%) [38]. Prior literature revealed that industrial workers were particularly vulnerable populations to depression and other mental health disorders given their low education and income, highly repetitive work, and constrained social support [6,39].…”
Section: Discussioncontrasting
confidence: 48%
“…In addition, it is important to recognise that having children could be a moderating factor on the relationship between shift work and HRPL [ 10 ] and that, in East Asian cultures, primary responsibility is commonly placed on mothers. Thus, women might have experienced higher levels of work–family conflict from shift work [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Kang et al, (2017), night work leads is known to disrupt the body's circadian rhythms, including the sleep-wake pattern. Most prominently, disrupted endogenous melatonin secretion can cause depression, anxiety, and sleep-wake cycle disorders (Rahman et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Shift work may also be associated with mental health (Kang et al, 2017). Although historically scientific literature on work and health has focused primarily on the occurrence of physical illnesses, in recent years the studies dealing with workers' mental health, or those linking physical and mental issues, have been increasing significantly (Sergio et al, 2017).…”
Section: Mental Healthmentioning
confidence: 99%